ATTITUDE OF BORROWERS REGARDING THE LENDING SERVICESOF BHUTAN DEVELOPMENT FINANCIAL CORPORATION LIMITED. - Dr. S. S. Jeyaraj & Dr. A. Prakash (International Journal of Research Science and Management, 2017)
The present study tries to explore and review the attitude of borrowers and opinion of employees regarding the lending services and performance of BDFCL. A total of 300 borrowers were selected out of 22 branches under various schemes to measure the level of satisfactionwith the help of Chi-square testand Factor Analytical Method. The study concluded that the majority of the borrowers (71.20%) have a medium level of satisfaction regarding the lending services of BDFCL. Locations of the plant, nature of the organization have influence on the level of satisfaction and age, while educations of the entrepreneurs do not influence the level of satisfaction. In factor analysis, ‘The loan application of the bank is short and it elicits only the information required for the grant of loan’, ‘margin money fixed by the bank is too high and borrowers find it difficult to pay the margin money’ are the variables influencing the attitude of the borrowers to the lending service of the BDFCL.The BDFCL officials should look into the real needs of the borrowers while processing the application for loans.